New observation of nanoscale interfacial evolution in micro Cu–Al wire bonds by in-situ high resolution TEM study. (1st April 2016) - Xu, Hui; Qin, Ivy; Clauberg, Horst; Chylak, Bob; Acoff, Viola L.
Abstract: Three types of interfacial nanostructure are identified in as-bonded Cu–Al bonds: (1) Cu/ 5 nm amorphous alumina layer/Al; (2) Cu/ 20 nm CuAl2 intermetallic particle/Al; and (3) Cu/Al. During annealing, in the areas of latter two types where alumina layer is fragmented, Cu9 Al4 and CuAl form as second and third intermetallic layers, and grow vertically and fast together with initial CuAl2 . In the area of first type where alumina layer is present, CuAl2 grows laterally and slowly via Cu diffusion through intermetallic compounds in the neighboring area where alumina is broken to reach Al. Cu–Al interdiffusion is dominated by Cu diffusion. Graphical abstract: